Nutritional evaluation and GC–MS analysis of bioactive compounds present in methanol extracts of dried fruit pericarp of garcinia pedunculata Roxb - Brahma, Jonali; Islary, Anuck; Ray, Subhajit (Journal of Food Technology Research, 2024)
This study was conducted to assess the nutritional and phytochemical properties of methanol extracts derived from the dried fruit pericarp of Garcinia pedunculata. Samples of the plant were obtained from the Bodoland Territorial Region (BTR), Assam, India due to the lack of study findings on Garcinia pedunculata from this region in the existing literature. Nutritional evaluation has revealed that Garcinia pedunculata is a notable source of various nutrients including fibre (15.67 ± 0.05 g/100g), protein (3.97 ± 0.06 g/100g), carbohydrates (80.10 ± 2.48 g/100g) and ascorbic acid (98.16 ± 4.46 mg/100g). Furthermore, the results of the gas chromatography coupled with mass spectrometry analysis (GC-MS) of the methanol extract revealed a diverse range of chemical compounds with both high and low molecular weight. GC-MS analysis showed bioactive compounds like cyclopentanecarboxylicacid, 2-oxo-, ethyl ester with a peak area of 23.60%followed by 1,3- dioxepane, 2-pentadecyl- with a peak area of 22.39%followed by N-[Carboxymethyl ]maleamic acid with a peak area of 10.37%and butanedioic acid,3-hydroxy-2,2-dimethyl, dimethyl ester, (R) with a peak area of 10.91%. The extracts exhibit significant amount of various naturally occurring bioactive compounds. Therefore, the existence of potential bioactive compounds and nutritional constituents can be suitably exploited for future studies.